Altered Biomechanics of the Normal Side and the Impact on Rehabilitation of the Affected Side in Patients with Hemiplegia: A Mini Review - Pallavi Lalchand Harjpal; Mohammed Irshad Qureshi; Rakesh Krishna Kovela; Moli Jai Jain (Journal of Clinical and Diagnostic Research, 2022)
Altered biomechanics is defined as the acquired alteration in the mechanics of the musculoskeletal system that leads to improper movement patterns. Hemiplegia is the reduction in strength or paralysis of one side of the body due to a stroke. The amount of involvement poststroke depends on the site of the lesion. There are various other neurological complications and associated symptoms, but the effect on biomechanics is due to alterations in the muscle strength of the unaffected side of stroke along with hemiplegia or paresis of the affected side. The unaffected side of stroke is considered to be the normal side and is thus, not considered in the treatment session, allowing it to lose its competencies, thus, the gait pattern is altered in poststroke survivors. To find the pertinent literature, electronic databases were searched using the terms “biomechanics” and “hemiplegia”. The resulting articles were reviewed, the bibliography was double-checked, and pertinent literature was added. The present review article discusses the alterations in the biomechanics of the normal side and the impact on rehabilitation of patients with hemiplegia. It also provides a newer outlook to focus also, on the normal side while rehabilitation, thus, enhancing early recovery.